Notifikasi Merger Sebagai Upaya Pengawasan KPPU Berdasarkan Hukum Nasional dan Perbandingan dengan Singapura - Alifia Jasmine (Jurnal Interpretasi Hukum, 2024)
Economic development in Indonesia is currently very rapid and has brought Indonesia into a wider open market and encouraged business competition. The existence of business competition also encourages a merger of companies to optimise their business. The government has also taken its role in regulating business competition through Law No. 5 of 1999 and establishing the KPPU as an institution that monitors the business competition climate in Indonesia. One of the things supervised by the KPPU is the act of merger carried out by a company, where there is an obligation to provide notification to the KPPU if the company merges with another company. This research uses a normative juridical method with a statute approach, conceptual approach and comparative approach. Secondary data used in this research is primary legal material (legislation), secondary legal material (doctrine), and tertiary legal material (encyclopaedia or public opinion), which will be analysed using juridical qualitative. The use of these three approaches is to answer problems regarding the concept of supervision by state institutions (KPPU) in supervising business competition, especially mergers, as well as to make comparisons between Indonesia and Singapore. Based on the research results, it was found that there are differences in regulatory regimes related to company merger notifications between Indonesia and Singapore, which can affect the ease of doing business in each country.